2020
DOI: 10.1016/j.mssp.2019.104863
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms behind slow photoresponse character of Pulsed Electron Deposited ZnO thin films

Abstract: Zinc Oxide (ZnO) semiconductor is ideal candidates for ultra-violet (UV) photodetector due to its promising optoelectronic properties. Photodetectors based on ZnO nanostructures show very high photoconductivity under UV light, but they are plagued by slow photo-response time as slow as several tens of hours, even more. Most of the studies claimed that atmospheric adsorbates such as water and oxygen create charge traps states on the surface and remarkably increase both the photoconductivity and response time, b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In the phototransients of ZnO films and nanowires, the surface adsorption of H 2 O and O 2 molecules plays a crucial role [15][16][17][18][19][20][21][23][24][25]. In this regard, we show in figure 4 that the electrical conduction in the Ag-Sb-S films was affected significantly by the surface condition.…”
Section: Photoconduction Propertiesmentioning
confidence: 79%
See 1 more Smart Citation
“…In the phototransients of ZnO films and nanowires, the surface adsorption of H 2 O and O 2 molecules plays a crucial role [15][16][17][18][19][20][21][23][24][25]. In this regard, we show in figure 4 that the electrical conduction in the Ag-Sb-S films was affected significantly by the surface condition.…”
Section: Photoconduction Propertiesmentioning
confidence: 79%
“…Similar slow photoresponses are known to occur for thin films and nanowires of ZnO [15][16][17][18][19][20][21]. The slow transients in the latter are attributed to the modifications in the transport of photocarriers due to environment effects caused by the surface of the films and nanowires and/or the bulk effects associated with crystalline defects [22][23][24][25]. That is, the charge transport in separating and uniting the photo-generated electrons and holes is affected by the electric fields induced by the attachment of water and/or oxygen molecules at the surface as well as by the trapping of the holes at deep-level defects [26].…”
Section: Introductionmentioning
confidence: 81%
“…The slow transition time in ZnO nanostructures can be attributed to the surface defects related to electron-trapping regions. It is also reported that O 2 and H 2 O molecules present in the environment can be trapped on the surface of n-type materials like ZnO to produce electron-trapping centers to slow down the transition time [ 44 ]. In the work reported herein the effect of H 2 O could also be amplified by the ability of CNF to scavenge H 2 O molecules from the environment.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, the trapping centers created during the doping process cause the reduction in photoresponse speed. [ 63 ] Typically, the device performance is highly affected by the total internal reflection in the hexagonal cross‐sectional tin‐doped CdS NWs. Numerous other factors, such as intrinsic material properties, defect tolerance, the influence of the ambient environment, and contact quality, all have an impact on the efficacy of PD devices.…”
Section: Surface Characterizationsmentioning
confidence: 99%